Silk fibroin silver nanowire composite material and preparation method and application thereof

By combining silver nanowires with high aspect ratio with silk fibroin, the problems of insufficient antibacterial properties of silk fibroin and easy accumulation of silver nanomaterials are solved, and the excellent antibacterial properties and biosafety of composite materials are achieved, and it is suitable for medical dressings and other fields.

CN119775786APending Publication Date: 2025-04-08QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411985097.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, silk fibroin has insufficient antibacterial properties when used alone, silver nanomaterials are prone to accumulate in biological bodies, long-term use may cause toxicity problems, and metal powdered materials are prone to aggregation in dressings, affecting dispersion uniformity and long-term antibacterial ability.

Method used

By first synthesizing silver nanowires with high aspect ratio and then compounding with silk fibroin, the biocompatibility of silk fibroin is successfully combined with the antibacterial properties of linear silver nanomaterials, so that the linear silver nanomaterials are evenly distributed in the silk fibroin membrane, which not only exerts the continuous antibacterial and anti-inflammatory effect, but also avoids potential toxicity problems.

Benefits of technology

It achieves excellent antibacterial properties of composite materials, improves biosafety and long-term use stability, and maintains the biocompatibility of silk fibroin, and is suitable for medical dressings and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775786A_ABST
    Figure CN119775786A_ABST
Patent Text Reader

Abstract

The invention discloses a silk fibroin silver nanowire composite material as well as a preparation method and application thereof. The preparation method of the silk fibroin silver nanowire composite material comprises the following steps: mixing polyol, silver nitrate and a surfactant for reaction to obtain a silver nanowire; and uniformly mixing the fibroin egg mortar solution with the silver nanowire to prepare the fibroin egg silver nanowire composite material. According to the preparation method, the silver nanowires are synthesized firstly and then compounded with the silk fibroin, the synthesized silver nanowires are stable in structure, the long-term use stability of the composite material is improved, the silver nanowires are evenly wrapped by the silk fibroin film, the silver release speed can be reduced, and the biological safety of the composite film is improved; by utilizing the excellent photoelectric effect of the silver nanowires, the composite material disclosed by the invention not only can be used as a medical dressing and the like, but also can be used for manufacturing flexible and stretchable wearable sensing equipment, sensing textile materials and the like, and is wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and specifically relates to a silk fibroin silver nanowire composite material and a preparation method and application thereof. Background Art

[0002] Skin wounds have always been a major hidden danger to human health. Although the human body has the ability to naturally repair damaged tissues, skin wound healing is a complex and highly organized physiological process involving a multi-step progression of four different but overlapping stages, including hemostasis, inflammation, proliferation, and tissue remodeling. The causes of non-healing wounds are multifaceted, including uncontrolled accumulation of reactive oxygen species (ROS), bacterial infection, microcirculatory disorders, and persistent inflammation. This slows down the healing of wounds and then rapidly expands to adjacent wound infection areas, further leading to ulcers, chronic wounds, skin diseases and inflammation in various parts of the body, and even death. In the field of biomedicine, the design and preparation of wound dressings is a critical task, the purpose of which is to accelerate wound healing and reduce the risk of infection.

[0003] In recent years, with the development of nanotechnology, silver nanomaterials have been widely studied due to their excellent conductivity and antibacterial properties. As a natural polymer protein, silk fibroin has been widely used in the biomedical field due to its good biocompatibility and biodegradability. Traditional wound dressing materials include gauze and cotton materials, which can provide basic protection but have certain limitations in promoting wound healing, antibacterial properties and comfort of use. Silk fibroin has been widely studied for use in wound dressings due to its excellent biocompatibility, adjustable biodegradability and excellent mechanical properties. However, despite the good biological activity of silk fibroin, its antibacterial properties are insufficient when used alone, which limits its effectiveness in certain clinical applications. As a significant antibacterial agent, silver nanomaterials are used in various medical devices and dressings to reduce bacterial infections and improve the antibacterial properties of dressings. However, silver nanomaterials tend to accumulate in the body, and long-term use may cause toxicity problems. Summary of the invention

[0004] The main purpose of the present invention is to provide a silk fibroin silver nanowire composite material and a preparation method and application thereof, so as to overcome the deficiencies in the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0006] One aspect of the present invention provides a method for preparing a silk fibroin silver nanowire composite material, comprising:

[0007] Mixing polyol, silver nitrate and surfactant to react and obtain silver nanowires;

[0008] The silk fibroin solution and the silver nanowires are uniformly mixed to prepare a silk fibroin silver nanowire composite material.

[0009] Another aspect of the present invention provides a silk fibroin silver nanowire composite material prepared by the aforementioned preparation method, wherein the mass content of silver nanowires in the silk fibroin silver nanowire composite material is 0.1-2wt%.

[0010] Another aspect of the present invention also provides a silk fibroin silver nanowire composite film, which is obtained by forming the aforementioned silk fibroin silver nanowire composite material, and the silk fibroin silver nanowire composite film includes a silk fibroin matrix and silver nanowires distributed inside the silk fibroin matrix.

[0011] Another aspect of the present invention also provides a method for preparing the aforementioned silk fibroin silver nanowire composite film, which comprises: spreading the silk fibroin silver nanowire composite material in a mold, and leaving it to stand at a temperature of 20-40°C and a humidity of 40-70% to obtain the silk fibroin silver nanowire composite film.

[0012] Another aspect of the present invention also provides the use of the aforementioned silk fibroin silver nanowire composite material or the aforementioned silk fibroin silver nanowire composite film in the fields of antibacterial, sensing, air filtration, water treatment or textiles.

[0013] Compared with the prior art, the technical solution of the present invention has at least the following advantages:

[0014] 1) The silk fibroin silver nanowire composite film provided by the present invention maintains the biocompatibility of silk fibroin, wherein the dispersed linear silver nanomaterials endow the composite film with excellent antibacterial properties, and can promote the recovery of wounds as a medical dressing. The silver nanowires are uniformly wrapped by the silk fibroin film, which can reduce the speed of silver release and improve the biosafety of the composite film. The synthesized silver nanowires have a stable structure, which improves the long-term stability of the composite material.

[0015] 2) The present invention adopts a one-pot method to more conveniently and greenly synthesize silver nanowires with a high aspect ratio. The high aspect ratio makes it lethal to microorganisms but almost innocuous to cells, thus ensuring its biocompatibility. No additives or adjuvants are used in the synthesis process, thus avoiding the toxic effects of additives and adjuvants remaining in medical dressings on wounds.

[0016] 3) Utilizing the excellent photoelectric effect and high aspect ratio of silver nanowires, the composite material provided by the present invention has good mechanical properties and can also be used to manufacture flexible, stretchable wearable sensing devices, sensing textile materials, etc.

[0017] 4) The preparation method provided by the present invention uses a solution film-forming method to evenly disperse the linear silver nanomaterials within the silk fibroin matrix. The combination method is simple and easy to control, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is a calculated distribution diagram of the diameter of the silver nanowires prepared in Example 1 of the present invention;

[0020] Figure 2 This is a SEM image of the silver nanowires prepared in Example 1 of the present invention;

[0021] Figure 3 This is a SEM image of the silk fibroin silver nanowire composite film prepared in Example 1 of the present invention;

[0022] Figure 4 This is a mapping image of the silver element in the silk fibroin silver nanowire composite film prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be more fully understood by reading the following specific embodiments. However, it should be understood that the specific embodiments disclosed below are only exemplary of the present invention, and the present invention can be embodied in various forms. Therefore, the specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0024] As one aspect of the technical solution of the present invention, a method for preparing a silk fibroin silver nanowire composite material includes:

[0025] Mixing polyol, silver nitrate and surfactant to react and obtain silver nanowires;

[0026] The silk fibroin solution and the silver nanowires are uniformly mixed to prepare a silk fibroin silver nanowire composite material.

[0027] In the prior art, when silk fibroin is used alone, its antibacterial performance is insufficient, and silver nanomaterials are easy to accumulate in the body, and long-term use may cause toxicity problems. When silk fibroin is directly compounded with silver nanomaterials, metal powder materials are easy to aggregate in the dressing, affecting the uniformity of the dispersion of silver nanomaterials in the composite material and the problem of long-term antibacterial ability. This limits the effect of silk fibroin nano-silver composite dressings in some clinical applications. The present invention successfully combines the biocompatibility of silk fibroin with the antibacterial properties of linear silver nanomaterials by first synthesizing silver nanowires with a high aspect ratio and then compounding them with silk fibroin, thereby overcoming the above-mentioned shortcomings, distributing linear silver nanomaterials in the silk fibroin film, and exerting the continuous antibacterial and anti-inflammatory effects of linear silver nanomaterials while avoiding potential toxicity problems.

[0028] In some embodiments, the reaction temperature is 140-180° C. and the reaction time is 30-60 min.

[0029] In some embodiments, the mass ratio of the polyol, silver nitrate and surfactant is (5-10):(1-2):(1-2).

[0030] In some embodiments, the polyol includes but is not limited to butanediol.

[0031] In some embodiments, the surfactant includes but is not limited to polyvinylpyrrolidone.

[0032] In some embodiments, the silk fibroin solution is obtained by mixing silk fibroin powder with water.

[0033] In some preferred embodiments, the content of silk fibroin in the silk fibroin solution is 6-12 wt %.

[0034] In some embodiments, the method for preparing the silk fibroin powder comprises: cutting natural silk cocoons into pieces, boiling and degumming them in a sodium carbonate solution to obtain degummed silk, and washing and drying the degummed silk to obtain the silk fibroin powder.

[0035] In some preferred embodiments, the method for preparing the silk fibroin powder comprises: dissolving the degummed silk with a lithium bromide solution at 50-70° C., and then performing dialysis, centrifugation, and freeze-drying treatments in sequence to obtain the silk fibroin powder.

[0036] In some more preferred embodiments, the dialysis treatment time is 48-72 hours.

[0037] In some more preferred embodiments, the rotation speed of the centrifugal treatment is 7500-10000r, and the time of the centrifugal treatment is 10-30min.

[0038] In some more preferred embodiments, the freeze-drying process lasts for 2-3 days.

[0039] In some embodiments, the preparation method includes: uniformly mixing the silk fibroin solution and the silver nanowire suspension to obtain the silk fibroin silver nanowire composite material.

[0040] In some preferred embodiments, the mass ratio of the silk fibroin solution to the silver nanowire suspension is 16:1-2:1.

[0041] In some preferred embodiments, the preparation method comprises: mixing the silver nanowires with a solvent to obtain the silver nanowire suspension.

[0042] In some more preferred embodiments, the solvent includes but is not limited to any one of deionized water, ethanol, and ultrapure water, or a combination of two or more thereof.

[0043] In some preferred embodiments, the content of silver nanowires in the silver nanowire suspension is 0.1-2 wt %.

[0044] As another aspect of the technical solution of the present invention, it relates to a silk fibroin silver nanowire composite material prepared by the aforementioned preparation method, wherein the mass content of silver nanowires in the silk fibroin silver nanowire composite material is 0.1-2wt%.

[0045] As another aspect of the technical solution of the present invention, a silk fibroin silver nanowire composite film is obtained by forming the aforementioned silk fibroin silver nanowire composite material, and the silk fibroin silver nanowire composite film includes a silk fibroin matrix and silver nanowires distributed inside the silk fibroin matrix.

[0046] In some embodiments, the silk fibroin silver nanowire composite film has a thickness of 50-500 μm.

[0047] As another aspect of the technical solution of the present invention, it also involves a method for preparing the aforementioned silk fibroin silver nanowire composite film, which comprises: spreading the silk fibroin silver nanowire composite material in a mold, and leaving it to stand for 1-3 days at a temperature of 20-40°C and a humidity of 40-70%, to obtain the silk fibroin silver nanowire composite film.

[0048] In some more specific embodiments, the method for preparing the silk fibroin silver nanowire composite film comprises:

[0049] S1. Preparation of silk fibroin powder:

[0050] Cut the natural silk cocoons into pieces, put them into a sodium carbonate solution, boil them in boiling water to remove the sericin on the outside of the silk, wash them with deionized water for multiple times to remove impurities and adsorbed ions, and dry them. Dissolve the degummed silk with a lithium bromide solution at 50-70°C to obtain a viscous liquid, pour it into a dialysis bag, and dialyze it at room temperature for 48-72 hours; remove the remaining impurities with a centrifuge, collect the supernatant, freeze-dry it in a freeze dryer, and grind it into powder to obtain silk fibroin powder;

[0051] S2. Preparation of linear silver nanomaterials:

[0052] Through a one-pot method, the temperature is 140-180° C., butanediol, silver nitrate and polyvinyl pyrrolidone are mixed and reacted for 30-60 minutes, and ethanol and deionized water are used for centrifugation at 7500-10000r, the supernatant is poured out and the precipitate is taken to prepare silver nanowires with uniform size for standby use; commercially available silver nanowires are often added with a variety of additives or auxiliary agents during the preparation process, and the steps are relatively cumbersome. The present invention adopts a one-pot method to more conveniently and greenly synthesize high aspect ratio silver nanowires. The silver nanoparticles are small in size and have strong mobility. They are easily phagocytosed by normal cells and endanger the normal function of the cells. The high aspect ratio makes them lethal to microorganisms but almost not lethal to cells, thereby ensuring their biocompatibility. In the synthesis process of the present invention, no additives and auxiliary agents are used, thereby avoiding the toxic effects of additives and auxiliary agents remaining in the medical dressing on the wound.

[0053] S3. Preparation of composite membrane:

[0054] The silk fibroin powder in step S1 is dissolved in water to obtain a silk fibroin solution, the silver nanowires in step S2 are dispersed in a solvent to obtain a silver nanowire suspension, the silk fibroin solution and the silver nanowire suspension are mixed in a certain proportion to form a uniform mixed solution, the mixed solution is evenly spread in a circular mold, and the mold containing the mixed solution is placed under constant temperature and humidity conditions to allow the silver nanowires to be wrapped inside by the silk fibroin, thereby preparing a composite film with a certain shape.

[0055] The silk fibroin silver nanowire composite film prepared by the present invention is transparent, which can facilitate the observation of wound healing without repeatedly uncovering it, reducing the chance of secondary damage to the wound. It is more suitable as a wound dressing that fits the skin for a long time, effectively promoting wound recovery, reducing inflammation and infection risks, and improving patient comfort and treatment effects.

[0056] As another aspect of the technical solution of the present invention, it also involves the application of the aforementioned silk fibroin silver nanowire composite material or the aforementioned silk fibroin silver nanowire composite film in the fields of antibacterial, sensing, air filtration, water treatment, textiles, etc.

[0057] In some embodiments, due to the multifunctionality of silk fibroin and linear silver nanomaterials, the composite material prepared by the present invention has a wide range of application potentials, and more application fields may be developed in the future. These applications can not only bring significant social and economic benefits, but also promote the development of related technical fields. For example, in the medical field: manufacturing medical implants, due to its good biocompatibility and biodegradability, the composite material can be used to manufacture various biomedical implants, such as joint replacement, soft tissue repair, etc. In the field of electronic sensors: manufacturing wearable sensors, using the excellent photoelectric effect of silver nanowires, can be used to manufacture flexible, stretchable electronic skin and other types of wearable sensing devices for monitoring physiological parameters such as body temperature and heart rate; manufacturing smart textiles, the conductivity and flexibility of the composite material make it suitable for manufacturing smart clothing, such as clothing that can monitor health status and environmental changes. In the antibacterial field: preparation of air filtration materials, the microporous structure and antibacterial properties of the composite material make it suitable for air filtration systems, which can effectively filter and kill bacteria and viruses in the air; preparation of water treatment materials, which can be used in water treatment equipment to remove bacteria in the water and provide safer drinking water; manufacture of antibacterial cotton textiles, the antibacterial properties of the composite material make it possible to be used to manufacture clothing with self-cleaning functions, reducing the need for maintenance and cleaning.

[0058] In summary, the present invention uses a solution film-forming method to place the linear silver nanomaterial inside the silk fibroin matrix. This combination is simple and easy to control, and is suitable for large-scale production. The composite material of the present invention combines the advantages of two materials, can promote the recovery of wounds, maintain the biocompatibility of silk fibroin, and ensure the structural stability of the linear silver nanomaterial. This method not only improves the long-term use stability of the composite material, but also allows it to be evenly wrapped by the silk fibroin film to reduce the speed of silver release, thereby improving the biosafety of the composite film. The addition of linear silver nanomaterials gives the composite material excellent antibacterial properties. This makes the material suitable for the medical and health field, such as making antibacterial medical fabrics, dressings, etc. Moreover, the biodegradability of silk fibroin allows the composite material to be environmentally friendly decomposed after use, reducing the environmental burden. This is particularly in line with the current trend of environmental protection and sustainable development.

[0059] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The reagents and raw materials used in the following examples are commercially available, and the experimental methods without specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0060] Example 1

[0061] A method for preparing a silk fibroin silver nanowire composite film comprises the following steps:

[0062] (1) Preparation of lyophilized silk fibroin powder

[0063] Cut the natural silk cocoons into pieces, put them into a 0.5wt% sodium carbonate solution, and boil them in boiling water to remove the sericin on the outside of the silk. Wash with deionized water three times to remove impurities and adsorbed ions and dry them. Dissolve the degummed silk with a 9M lithium bromide solution at 65°C to obtain a viscous liquid, pour it into a dialysis bag, and dialyze it at room temperature for 72 hours. Centrifuge for 20 minutes to remove the remaining impurities, collect the supernatant, freeze-dry it in a freeze dryer for 3 days, and then grind it into powder to obtain silk fibroin powder.

[0064] (2) Preparation of linear silver nanomaterials

[0065] Through the one-pot method, the temperature is 170℃, butanediol, silver nitrate, polyvinyl pyrrolidone (mass ratio is 5:1:1) are reacted for 30 minutes, and ethanol and deionized water are centrifuged at 10000r, the supernatant is discarded and the precipitate is taken to prepare silver nanowires with uniform size for use. The diameter calculation distribution diagram of the obtained silver nanowires can be found in Figure 1 , its SEM image can be found at Figure 2 .

[0066] (3) Preparation of composite membrane

[0067] Mix a silk fibroin aqueous solution (8wt%) and a silver nanowire aqueous suspension (2wt%), with the mass ratio of the silk fibroin aqueous solution to the silver nanowire aqueous suspension being 4:1, to form a uniform mixed solution; spread the mixed solution evenly in a circular mold; place the mold containing the mixed solution at a constant temperature and humidity (37°C, relative humidity 55%) for 1 day to allow the silver nanowires to be wrapped inside by the silk fibroin, and prepare a silk fibroin silver nanowire composite film with a certain shape. The thickness of the composite film is 300μm. For the SEM image of the silk fibroin silver nanowire composite film prepared in this example, see Figure 3 , the mapping image of silver element in the composite film can be found in Figure 4 .

[0068] Example 2

[0069] A method for preparing a silk fibroin silver nanowire composite film comprises the following steps:

[0070] (1) Preparation of lyophilized silk fibroin powder

[0071] Cut the natural silk cocoons into pieces, put them into a 0.6wt% sodium carbonate solution, and boil them in boiling water to remove the sericin on the outside of the silk. Wash them with deionized water three times to remove impurities and adsorbed ions and dry them. Dissolve the degummed silk in a 9M lithium bromide solution at 65°C to obtain a viscous liquid, pour it into a dialysis bag, and dialyze it at room temperature for 72 hours. Centrifuge it for 20 minutes to remove the remaining impurities, collect the supernatant, freeze-dry it in a freeze dryer for 3 days, and then grind it into powder to obtain silk fibroin powder.

[0072] (2) Preparation of linear silver nanomaterials

[0073] Through a one-pot method, at a temperature of 170°C, butanediol, silver nitrate, and polyvinyl pyrrolidone (mass ratio of 8:1.5:1.5) were reacted for 30 minutes, and then centrifuged at 10,000 r with ethanol and deionized water. The supernatant was discarded and the precipitate was taken to prepare silver nanowires of uniform size for use.

[0074] (3) Preparation of composite membrane

[0075] The silk fibroin aqueous solution (8wt%) and the silver nanowire aqueous suspension (1wt%) were mixed, the mass ratio of the silk fibroin aqueous solution to the silver nanowire aqueous suspension was 8:1, to form a uniform mixed solution; the mixed solution was evenly spread in a circular mold; the mold with the mixed solution was placed under constant temperature and humidity conditions (37°C, relative humidity 55%) for 1 day, so that the silver nanowires were wrapped inside by the silk fibroin, and a silk fibroin silver nanowire composite film with a certain shape was prepared. The thickness of the composite film is 300μm.

[0076] Example 3

[0077] A method for preparing a silk fibroin silver nanowire composite film comprises the following steps:

[0078] (1) Preparation of lyophilized silk fibroin powder

[0079] Cut the natural silk cocoons into pieces, put them into a 0.5wt% sodium carbonate solution, and boil them in boiling water to remove the sericin on the outside of the silk. Wash with deionized water three times to remove impurities and adsorbed ions and dry them. Dissolve the degummed silk in a 10M lithium bromide solution at 65°C to obtain a viscous liquid, pour it into a dialysis bag, and dialyze it at room temperature for 72 hours. Centrifuge for 20 minutes to remove the remaining impurities, collect the supernatant, freeze-dry it in a freeze dryer for 3 days, and then grind it into powder to obtain silk fibroin powder.

[0080] (2) Preparation of linear silver nanomaterials

[0081] Through a one-pot method, butanediol, silver nitrate, and polyvinyl pyrrolidone (mass ratio of 10:1:1) were reacted at 170°C for 30 minutes, and then centrifuged at 10000r with ethanol and deionized water. The supernatant was discarded and the precipitate was taken to prepare silver nanowires of uniform size for use.

[0082] (3) Preparation of composite membrane

[0083] The silk fibroin aqueous solution (8wt%) and the silver nanowire aqueous suspension (0.5wt%) were mixed, and the mass ratio of the silk fibroin aqueous solution to the silver nanowire aqueous suspension was 16:1 to form a uniform mixed solution; the mixed solution was evenly spread in a circular mold; the mold with the mixed solution was placed under constant temperature and humidity conditions (37°C, relative humidity 55%) for 1 day, so that the silver nanowires were wrapped inside by the silk fibroin, and a silk fibroin silver nanowire composite film with a certain shape was prepared. The thickness of the composite film is 300μm.

[0084] Example 4

[0085] A method for preparing a silk fibroin silver nanowire composite film comprises the following steps:

[0086] (1) Preparation of lyophilized silk fibroin powder

[0087] Cut the natural silk cocoons into pieces, put them into a 0.5wt% sodium carbonate solution, and boil them in boiling water to remove the sericin on the outside of the silk. Wash with deionized water three times to remove impurities and adsorbed ions and dry them. Dissolve the degummed silk with a 9M lithium bromide solution at 50°C to obtain a viscous liquid, pour it into a dialysis bag, and dialyze it at room temperature for 48 hours. Centrifuge for 10 minutes to remove the remaining impurities, collect the supernatant, freeze-dry it in a freeze dryer for 2 days, and then grind it into powder to obtain silk fibroin powder.

[0088] (2) Preparation of linear silver nanomaterials

[0089] Through a one-pot method, butanediol, silver nitrate, and polyvinyl pyrrolidone (mass ratio of 5:1:1) were reacted at 140°C for 60 minutes, and then centrifuged at 7500r with ethanol and deionized water. The supernatant was discarded and the precipitate was taken to prepare silver nanowires of uniform size for use.

[0090] (3) Preparation of composite membrane

[0091] A silk fibroin aqueous solution (6wt%) and a silver nanowire aqueous suspension (0.1wt%) were mixed, with the mass ratio of the silk fibroin aqueous solution to the silver nanowire aqueous suspension being 2:1, to form a uniform mixed solution; the mixed solution was evenly spread in a circular mold; the mold containing the mixed solution was placed at a constant temperature and humidity (30°C, relative humidity 40%) for 3 days, so that the silver nanowires were wrapped inside by the silk fibroin, and a silk fibroin silver nanowire composite film with a certain shape was prepared. The thickness of the composite film was 50μm.

[0092] Example 5

[0093] A method for preparing a silk fibroin silver nanowire composite film comprises the following steps:

[0094] (1) Preparation of lyophilized silk fibroin powder

[0095] Cut the natural silk cocoons into pieces, put them into a 0.5wt% sodium carbonate solution, and boil them in boiling water to remove the sericin on the outside of the silk. Wash them with deionized water three times to remove impurities and adsorbed ions and dry them. Dissolve the degummed silk with a 9M lithium bromide solution at 70°C to obtain a viscous liquid, pour it into a dialysis bag, and dialyze it at room temperature for 60 hours. Centrifuge it for 15 minutes to remove the remaining impurities, collect the supernatant, freeze-dry it in a freeze dryer for 3 days, and then grind it into powder to obtain silk fibroin powder.

[0096] (2) Preparation of linear silver nanomaterials

[0097] Through the one-pot method, the temperature is 180℃, butanediol, silver nitrate, polyvinyl pyrrolidone (mass ratio is 5:2:2) are reacted for 40 minutes, and ethanol and deionized water are centrifuged at 8000r, the supernatant is discarded and the precipitate is taken to prepare silver nanowires with uniform size for use. The diameter calculation distribution diagram of the obtained silver nanowires can be found in Figure 1 .

[0098] (3) Preparation of composite membrane

[0099] A silk fibroin aqueous solution (12wt%) and a silver nanowire aqueous suspension (2wt%) were mixed, with the mass ratio of the silk fibroin aqueous solution to the silver nanowire aqueous suspension being 4:1, to form a uniform mixed solution; the mixed solution was evenly spread in a circular mold; the mold containing the mixed solution was placed at a constant temperature and humidity condition (25°C, relative humidity 70%) for 2 days, so that the silver nanowires were wrapped inside by the silk fibroin, and a silk fibroin silver nanowire composite film with a certain shape was prepared. The thickness of the composite film was 500μm.

[0100] Comparative Example 1

[0101] A method for preparing a silk fibroin silver nanomaterial composite film comprises the following steps:

[0102] (1) Preparation of lyophilized silk fibroin powder

[0103] Cut the natural silk cocoons into pieces, put them into 0.5wt% sodium carbonate solution, and boil them in boiling water to remove the sericin on the outside of the silk. Wash with deionized water 3 times to remove impurities and adsorbed ions and dry them. Dissolve the degummed silk in 9M lithium bromide solution at 65°C to obtain a viscous liquid, pour it into a dialysis bag, and dialyze it at room temperature for 72 hours. Centrifuge for 20 minutes to remove the remaining impurities, collect the supernatant, freeze-dry it in a freeze dryer for 3 days, and then grind it into powder to obtain silk fibroin powder.

[0104] (2) Preparation of silk fibroin film

[0105] The silk fibroin aqueous solution (8wt%) and the silver nanopowder aqueous suspension (0.5wt%) were mixed, and the mass ratio of the silk fibroin aqueous solution to the silver nanopowder aqueous suspension was 16:1 to form a uniform mixed solution; the mixed solution was evenly spread in a circular mold; the mold containing the mixed solution was placed under constant temperature and humidity conditions (37°C, relative humidity 55%) for 1 day, so that the silver nanopowder was wrapped inside by the silk fibroin, and a composite film with a certain shape was prepared. The thickness of the composite film was 300μm. The obtained composite film was brittle and had poor flexibility.

[0106] In summary, the present invention effectively combines silk fibroin with silver nanowires, which can improve the mechanical properties and functionality of the composite material.

[0107] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0108] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a silk fibroin silver nanowire composite material, characterized in that: include: Mixing polyol, silver nitrate and surfactant to react and obtain silver nanowires; The silk fibroin solution and the silver nanowires are evenly mixed to prepare a silk fibroin silver nanowire composite material.

2. The preparation method according to claim 1, characterized in that: The reaction temperature is 140-180°C and the reaction time is 30-60min; And / or, the mass ratio of the polyol, silver nitrate and surfactant is (5-10):(1-2):(1-2); and / or, the polyol comprises butanediol; And / or, the surfactant comprises polyvinyl pyrrolidone.

3. The preparation method according to claim 1, characterized in that: The silk fibroin solution is obtained by mixing silk fibroin powder with water; Preferably, the content of silk fibroin in the silk fibroin solution is 6-12 wt %.

4. The preparation method according to claim 3, characterized in that: The preparation method of the silk fibroin powder comprises: cutting natural silk cocoons into pieces, boiling and degumming in a sodium carbonate solution to obtain degummed silk, and washing and drying the degummed silk to obtain the silk fibroin powder.

5. The preparation method according to claim 4, characterized in that: The preparation method of the silk fibroin powder comprises: dissolving the degummed silk with a lithium bromide solution at 50-70° C., and then performing dialysis, centrifugation, and freeze-drying treatments in sequence to obtain the silk fibroin powder; Preferably, the dialysis treatment time is 48-72h; Preferably, the rotation speed of the centrifugal treatment is 7500-10000r, and the time of the centrifugal treatment is 10-30min; Preferably, the freeze-drying treatment lasts for 2-3 days.

6. The preparation method according to claim 1, characterized in that: include: The silk fibroin solution and the silver nanowire suspension are uniformly mixed to obtain the silk fibroin silver nanowire composite material; Preferably, the mass ratio of the silk fibroin solution to the silver nanowire suspension is 16:1-2:1; Preferably, the silver nanowires are mixed with a solvent to obtain the silver nanowire suspension; Particularly preferably, the solvent comprises any one of water and ethanol or a combination of both; Preferably, the content of silver nanowires in the silver nanowire suspension is 0.1-2 wt %.

7. A silk fibroin silver nanowire composite material prepared by the preparation method according to any one of claims 1 to 6, wherein the mass content of silver nanowires in the silk fibroin silver nanowire composite material is 0.1-2wt%.

8. A silk fibroin silver nanowire composite film, characterized in that: The silk fibroin silver nanowire composite material according to claim 6 is formed and obtained, wherein the silk fibroin silver nanowire composite film comprises a silk fibroin matrix and silver nanowires distributed inside the silk fibroin matrix; Preferably, the thickness of the silk fibroin silver nanowire composite film is 50-500 μm.

9. The method for preparing the silk fibroin silver nanowire composite film according to claim 8, characterized in that: include: The silk fibroin silver nanowire composite material is spread in a mold, and allowed to stand for 1-3 days at a temperature of 20-40° C. and a humidity of 40-70%, to obtain the silk fibroin silver nanowire composite film.

10. Application of the silk fibroin silver nanowire composite material according to claim 7 or the silk fibroin silver nanowire composite film according to claim 8 in the fields of antibacterial, sensing, air filtration, water treatment or textiles; Preferably, the application includes: application of the silk fibroin silver nanowire composite material or the silk fibroin silver nanowire composite film in the preparation of medical implant materials, electronic sensors, air filtration materials, water treatment materials or antibacterial textile materials; Particularly preferably, the application includes: application of the silk fibroin silver nanowire composite material or the silk fibroin silver nanowire composite film in the preparation of wearable sensing devices, antibacterial cotton textiles or smart textiles.

Citation Information

Patent Citations

  • Silver nanothread / silk fibroin composite fiber and preparation method thereof

    CN110230113A

  • Transient electronic device taking silk fibroin film as flexible substrate and preparation method of transient electronic device

    CN111621041A